Effect of solution and aging processes on the mechanical properties of 6016 aluminum alloy and multi-objective optimization - MA Yan-wei; WANG Bao-yu; XIAO Wen-chao; ZHOU Jing; KANG Yi (工程科学学报)
As a part of heat treatment processes, solution treatment and aging treatment have a great influence on the mechanical properties of 6016 aluminum alloy. In this article, solution temperature, solution time, aging temperature and aging time were taken as parameters to design a heat treatment scheme by central composite design (CCD). At room temperature, the yield strength, elongation, and Vickers hardness of specimens were measured by mechanical testing. The second-generation non-dominated sorting genetic algorithm (NSGA-Ⅱ) solves the shortcomings of the first-generation algorithm, such as the difficulty in parameter selection and low efficiency. In this study, the response surface model derived was used as the objective function to perform the multi-objective optimization by means of NSGA-Ⅱ. After calculation, the Pareto solutions were obtained to filtrate out the solution with comprehensive performance, and then, to acquire the corresponding parameters of the solution and aging process.